An Empirical Exploration of Leisure-Related Themes and Potential Constraints across Descriptions of Serial Homicide Cases. (2nd January 2020) - Williams, D J; Thomas, Jeremy N.; Arntfield, Michael
ABSTRACT: Forensic experts commonly state that many serial homicide offenders kill for the pleasure of it. At the same time, a small number of leisure scientists have suggested that serial murder may be a particular form of deviant leisure. Despite such suggestions, there has been little scholarly exploration of serial homicide from a leisure science perspective. This exploratory study adds to the existing literature by analyzing content of multiple key texts and documents that describe a large number of serial homicide cases in order to explore an understanding of murder as potential leisure. Leisure-related themes that emerged across case descriptions were (a) serial murder as a game, (b) murder for thrills and intense sensations, (c) murder for simple enjoyment and fun, and (d) murder as unique personal celebration. Subsequently, possible intrapersonal, interpersonal, and structural constraints to serial murder as possible leisure were identified. Implications for future research are also discussed.